Research on Intracranial Atherosclerosis from the East and West: Why Are the Results Different? - Jong S. Kim (Journal of Stroke, 2014)
Intracranial atherosclerosis (ICAS) is a major cause of stroke worldwide and is more common in Asians than Caucasians. The study results from the East and West are generally similar, but notable differences exist. For example, studies from the East have reported that ICAS is associated with young age, whereas ICAS seems to be associated with old age in the West. Studies from the East have strongly suggested that mild ICAS associated with branch occlusion is one of the main causes of single subcortical infarction, whereas this aspect has not been considered in stroke classification systems developed in the West. While clopidogrel is commonly used in patients with large artery disease in the West, cilostazol has been more extensively studied and commonly used in ICAS patients in the East. A randomized controlled study from the West reported negative results regarding the efficacy of stenting in ICAS patients due largely to a relatively high rate of periprocedural adverse events, whereas research papers from the East have reported a relatively lower rate of complications. Studies to narrow these East-West gaps should be performed, including risk factor studies using homogenous ethnic populations, studies investigating appropriate classification systems, drug trials in different ethnic populations, and rigorous high standard randomized controlled studies on the efficacy of stenting in Eastern populations.